Corrosion of Carbon Steel in CO2-Saturated Brines Investigated by Rotating Disk Electrode and Scanning Vibrating Electrode Technique. (7th July 2017) - Feng, Ruishu; Ziomek-Moroz, Margaret; Tylczak, Joseph H; Ohodnicki, Paul R
Abstract : CO2 makes carbon steels susceptible to corrosion and failure during oil and natural gas exploration, production, transmission, and processing as well as in CO2 capture and sequestration systems. CO2 corrosion of carbon steel grade X65 was investigated in deaerated 3.5 wt% NaCl solutions from pH 4 to 7 at 30 o C in a rotating disk electrode system. The effects of CO2, pH, and mass transport were studied using in situ electrochemical methods. The CR increased by 20 times by CO2 through facilitating anodic and cathodic reactions. The CR decreased at higher pH mostly due to suppressed cathodic reactions. Higher rotation rate slightly increased CR without changing the reaction mechanism. The cathodic reaction was limited by slow hydration of CO2 . The scanning vibrating electrode technique showed a growing pit after corroded in the N2 deaerated solution, and the corrosion products covered surface served as the cathode in the CO2 saturated solution.